Discopyge castelloi, Castello's Apron Numbfish - Pollom, R. (2020)
Castello's Apron Numbfish (Discopyge castelloi) is a small (to at least 31 cm total length) ray that occurs in the Southwest Atlantic from Necochea, Buenos Aires, to Camarones, Chubut, Argentina. It inhabits the inner continental shelf at depths of 35–56 m. Its depth range suggests that it is exposed to commercial and artisanal demersal trawl fisheries. Commercial fishing began in Argentina in the late 1800s, became industrialized after World War II, and increased rapidly in the 1980s. By 1992 there were over 300 coastal trawlers. This number increased to over 400 in 2015, and the number of fishing trips undertaken by that fleet nearly doubled from over 7,600 to nearly 14,000 over that time frame. The overall number of fishing vessels in operation in Argentina has grown from under 300 in 1990 to nearly 1,000 in 2015. This species has however been caught only rarely, and may have either a low catchability or a depth range deeper than is currently known. Further research is needed on distribution, life history, population size and trend, and threats. Since it is unknown whether fishing is causing a population reduction, there is currently inadequate information available to assess Castello's Apron Numbfish beyond Data Deficient.